Migrația ca fenomen social: perspective și abordări teoretice transdisciplinare - Cristina Haruţa (Revista Transilvană de Ştiinţe Administrative, 2018)
Against the backdrop of the most recent political and economic consequences generated by the migration issues in the European realm, the necessity to understand this complex social phenomenon resurfaces as a topic that both politicians and scholars worldwide attempt to approach from different angles and perspectives. In this article, the continuously growing literature on international migration is revised and ‘revisited’ with the purpose of providing an overview of the most important and relevant theories and conceptual approaches outlined by various renowned authors. Ultimately, a sound understanding of the determinants and effects of migration on a theoretical level can deliver the grounds for improved ways of predicting and tackling migration issues.